Consumer segmentation within the sharing economy: The case of Airbnb - Lutz, Christoph; Newlands, Gemma (Journal of business research, 2018)
The sharing economy is a global phenomenon with rapid growth potential. While research has begun to explore segmentation between users and non-users, only limited research has looked at consumer segmentation within sharing economy services. In this paper, we build on this research gap by investigating consumer segmentation within a single sharing economy platform: Airbnb. Utilizing a mixed methods approach, with both a quantitative survey and a qualitative content analysis of Airbnb listings, we compare two different types of accommodation offered on Airbnb: shared room and entire home. Our findings indicate that within a single platform, the variety between offerings can create distinct consumer segments based on both demographics and behavioral criteria. We also find that Airbnb hosts use marketing logic to target their listings towards specific consumer segments. However, there is not, in all cases, strong alignment between consumer segmentation and host targeting, leading to potentially reduced matching efficiency. •Users of shared rooms and entire homes on Airbnb are substantially different.•Income, education, gender, and travel modality predict accommodation choice.•Airbnb hosts strongly target listings for customer segments, such as for age.•Guest choice and host targeting do not align, leading to potential inefficiency.